Perbandingan Antara Metode NCSA Dan Metode Analisa Komponen Bina Marga Dalam Menentukan Tebal Perkerasan - Yuslan Irianie (INFO-TEKNIK, 2007)
There are some method to design flexible pavement, two of them are Bina Marga Component Analysis and NCSA method. Both of these methods really have difference. Thus, writer was interested to have a research. The aim of this research is compare both of them on the depth of pavement design.On this paper both of this method used to design Trisakti–Liang Anggang trip by A. Yani higway.On this study, NCSA method resulted  D1 = 5 cm, D2 = 10 cm, D3 = 17,5 cm and Bina Marga Component Analysis method resulted  D1 =  5 cm, D2 = 10 cm,  D3 = 27 cm.